Body dimensions and proportions in the differential diagnosis of child growth retardation - Łysoń-Wojciechowska, Grażyna; Romer, Tomasz E.; Skawiński, Waldemar (Anthropological Review, 1997)
This study was aimed at determining the similarities and differences with regard to body build traits between two groups of short-statured children: the first one including children with growth retardation related to the growth hormone deficiency and the second one comprising of children with normal secretion of the growth hormone. Subsequently the traits useful in the differential diagnostics of growth retardation were selected. Anthropometric measurements were taken from 273 short-statured non-treated children aged from 3 to 17 years (73 girls and 200 boys). The children were divided into 6 clinical groups on the basis of the clinical picture and the results of stimulation tests assessing the pituitary reserve for growth hormone secretion. The clinical groups were differentiated using a specifically developed anthropometric test based on 9 calendar age traits (height, weight, BMI, length of upper and lower limbs, trunk length, shoulders breadth, hips breadth and chest breadth) and 4 developmental age traits (length and circumference of the head, chest circumference, thigh circumference) and the calculated value of arm fat content and the average stature of the parents.